Análisis de la producción y productividad del cultivo de pitahaya en los cantones Quevedo, Mocache y Ventanas, año 2015. - Vera Sevillano, Wendy Alexandra (2016)
In the province of Los Ríos there is much ignorance about fruit pitahaya by the lack of information on the production process and high implementation costs that prevent farmers take the option of cultivating this fruit, so this research was conducted in order to determine the production and productivity of dragon fruit cultivation in Quevedo, Mocache and Windows, belonging to the province of Los Rios, cantons 2015 a survey was conducted with objective questions to obtain specific data on crop management, production, costs, etc., which were of great interest and importance to the development of research, considering as universe existenrtes dragon fruit producers in areas (eight), who provided information about the red dragon fruit cultivation. The main results of the investigation showed that planting represents a cost ranging from $ 1706.50 to $ 2270.00, being higher in the area of Quevedo, and lower in Mocache, for controlling farmers spend $ 60.00 per year when perform chemical control, whereas when it is $ 90.00 to $ 144.00. The cost of soil fertilization ranges from $ 80.00 when manure is used, and can reach up to $ 120.00 when using synthetic fertilizers. When foliar organic fertilizers are used is spending $ 160.00 to $ 196.00, while when using synthetic fertilizers foliar spend between $ 98.00 and $ 116.00. Pest control represents an expense between $ 9.60 and $ 13.00. In the canton Quevedo the annual cost of harvest concept fluctuates between $ 510.00 and $ 624.00, while in Mocache going from $ 510.00 to $ 520.00, in Windows spend between $ 612.00 and $ 624.00. The price paid for the lease of land per year is from $ 600.00 to $ 900.00. The amount of the total cost of production is lower in the area where Mocache fluctuates between $ 1258.63 and $ 1315.66, while in Quevedo is between $ 1382.63 and $ 1625.90.El average yield varies between 2890 and 4030 Kg / ha , being higher in the farms in the area Quevedo. The economic benefit ranges from $ 2014.12 $ 3765.52 per hectare and year, being higher when there is no participation of the intermediary, ie the yield per hectare is between 87 and 181% annually.